当前位置:网站首页>最全常用高数公式
最全常用高数公式
2022-07-06 22:42:00 【全栈O-Jay】
文章目录
1 等价无穷小 ( x → 0 x\to 0 x→0)
s i n x ∼ x sinx\sim x sinx∼x, t a n x ∼ x tanx\sim x tanx∼x, a r c s i n x ∼ x arcsinx\sim x arcsinx∼x, a r c t a n x ∼ x arctanx\sim x arctanx∼x, e x − 1 ∼ x e^x -1\sim x ex−1∼x, I n ( 1 + x ) ∼ x In(1+x)\sim x In(1+x)∼x,
a x − 1 = e x I n a − 1 ∼ x I n a a^x-1= e^{xIna}-1\sim xIna ax−1=exIna−1∼xIna, 1 − c o s x ∼ 1 2 x 2 1-cosx\sim \frac{1}{2}x^2 1−cosx∼21x2, ( 1 + x ) a − 1 ∼ a x (1+x)^a -1\sim ax (1+x)a−1∼ax,
小 + 大 ∼ 大 小+大\sim 大 小+大∼大, ∫ 0 x f ( t ) d t ∼ x \int_{0}^{x}f(t)dt\sim x ∫0xf(t)dt∼x
2 常用公式
2.1 和式夹逼准则的两个思路
n → ∞ : n ⋅ u m i n ≤ ∑ i = 1 n u i ≤ n ⋅ u m a x n → 有 限 : 1 ⋅ u m a x ≤ ∑ i = 1 n u i ≤ n ⋅ u m a x n\to \infty : n\cdot u_{min}\leq \sum\limits_{i=1}^{n}u_i \leq n\cdot u_{max}\\ n\to 有限 : 1\cdot u_{max}\leq \sum\limits_{i=1}^{n}u_i \leq n\cdot u_{max} n→∞:n⋅umin≤i=1∑nui≤n⋅umaxn→有限:1⋅umax≤i=1∑nui≤n⋅umax
2.2 小基础
- ( a + b ) 3 = a 3 + 3 a 2 b + 3 a b 2 + b 3 (a+b)^3 = a^3+ 3a^2b + 3ab^2 + b^3 (a+b)3=a3+3a2b+3ab2+b3
- a 3 − b 3 = ( a − b ) ( a 2 + a b + b 3 ) a^3-b^3 = (a-b)(a^2 + ab + b^3) a3−b3=(a−b)(a2+ab+b3)
- ( a + b ) n = ∑ k = 0 n C n k a n − k b k (a+b)^n = \sum\limits_{k=0}^{n}C_n^ka^{n-k}b^k (a+b)n=k=0∑nCnkan−kbk
- ∑ k = 1 n k 2 = n ( n + 1 ) ( 2 n + 1 ) 6 \sum\limits_{k=1}^{n}k^2 = \frac{n(n+1)(2n+1)}{6} k=1∑nk2=6n(n+1)(2n+1)
- ∑ n = 1 ∞ 1 n 2 = π 2 6 \sum\limits_{n=1}^{\infty}\frac{1}{n^2} = \frac{\pi ^2}{6} n=1∑∞n21=6π2
2.3 一元二次方程解
X 1 , 2 = − b ± b 2 − 4 a c 2 a , X 1 + X 2 = − b a , X 1 X 2 = a c , 顶 点 : ( − b 2 a , c − b 2 4 a ) X_{1,2} = \frac{-b\pm \sqrt{b^2-4ac}}{2a}, X_1 + X_2 = -\frac{b}{a}, X_1X_2 = \frac{a}{c},\\顶点: (-\frac{b}{2a} , c-\frac{b^2}{4a}) X1,2=2a−b±b2−4ac,X1+X2=−ab,X1X2=ca,顶点:(−2ab,c−4ab2)
3 * \bigstar *常用展开公式 * \bigstar *
- e x = 1 + x + x 2 2 ! + ⋯ = ∑ n = 0 ∞ x n n ! e^x = 1+x+\frac{x^2}{2!}+\cdots =\sum\limits_{n=0}^{\infty}\frac{x^n}{n!} ex=1+x+2!x2+⋯=n=0∑∞n!xn
- I n ( 1 + x ) = x − x 2 2 + ⋯ = ∑ n = 0 ∞ ( − 1 ) n − 1 x n n ( − 1 < x ≤ 1 ) In(1+x) = x-\frac{x^2}{2}+\cdots =\sum\limits_{n=0}^{\infty}(-1)^{n-1}\frac{x^n}{n}\quad (-1<x\leq 1) In(1+x)=x−2x2+⋯=n=0∑∞(−1)n−1nxn(−1<x≤1)
- I n ( 1 − x ) = − ∑ n = 0 ∞ x n n ( − 1 < x ≤ 1 ) In(1-x) = -\sum\limits_{n=0}^{\infty}\frac{x^n}{n}\quad (-1<x\leq 1) In(1−x)=−n=0∑∞nxn(−1<x≤1)
- 1 1 − x = 1 + x + x 2 + ⋯ = ∑ n = 0 ∞ x n ∣ x ∣ < 1 \frac{1}{1-x} = 1+x+x^2+\cdots =\sum\limits_{n=0}^{\infty}x^n\quad \mid x\mid <1 1−x1=1+x+x2+⋯=n=0∑∞xn∣x∣<1
- s i n x = x − x 3 3 ! + ⋯ = ∑ n = 0 − ∞ ( − 1 ) n x 2 n + 1 ( 2 n + 1 ) ! sinx = x-\frac{x^3}{3!}+\cdots =\sum\limits_{n=0}^{-\infty}(-1)^{n}\frac{x^{2n+1}}{(2n+1)!} sinx=x−3!x3+⋯=n=0∑−∞(−1)n(2n+1)!x2n+1
- c o s x = 1 − x 2 2 ! + ⋯ = ∑ n = 0 − ∞ ( − 1 ) n x 2 n ( 2 n ) ! cosx = 1-\frac{x^2}{2!}+\cdots =\sum\limits_{n=0}^{-\infty}(-1)^{n}\frac{x^{2n}}{(2n)!} cosx=1−2!x2+⋯=n=0∑−∞(−1)n(2n)!x2n
- t a n x = x + x 3 3 + O ( x 3 ) tanx = x+\frac{x^3}{3}+O(x^3) tanx=x+3x3+O(x3)
- a r c s i n x = x + x 3 6 + O ( x 3 ) arcsinx = x+\frac{x^3}{6}+O(x^3) arcsinx=x+6x3+O(x3)
- a r c t a n x = x − x 3 3 + O ( x 3 ) = ∑ n = 0 ∞ ( − 1 ) n x 2 n + 1 2 n + 1 arctanx = x-\frac{x^3}{3}+O(x^3) = \sum\limits_{n=0}^{\infty}(-1)^{n}\frac{x^{2n+1}}{2n+1} arctanx=x−3x3+O(x3)=n=0∑∞(−1)n2n+1x2n+1
- e x − e − x 2 = ∑ n = 0 ∞ x 2 n + 1 ( 2 n + 1 ) ! \frac{e^x-e^{-x}}{2} = \sum\limits_{n=0}^{\infty}\frac{x^{2n+1}}{(2n+1)!} 2ex−e−x=n=0∑∞(2n+1)!x2n+1
- e x + e − x 2 = ∑ n = 0 ∞ x 2 n ( 2 n ) ! \frac{e^x+e^{-x}}{2} = \sum\limits_{n=0}^{\infty}\frac{x^{2n}}{(2n)!} 2ex+e−x=n=0∑∞(2n)!x2n
- ( 1 + x ) a = 1 + a x + a ( a − 1 ) 2 x 2 + O ( x 2 ) (1+x)^a = 1+ax+\frac{a(a-1)}2{x^2} + O(x^2) (1+x)a=1+ax+2a(a−1)x2+O(x2)
4 常用不等式
- a r c t a n x < x < a r c s i n x ( 0 ≤ x ≤ 1 ) arctanx < x < arcsinx \quad (0\leq x\leq 1) arctanx<x<arcsinx(0≤x≤1)
- e x ≥ x + 1 ( ∀ x ) e^x \geq x+1\quad (∀x) ex≥x+1(∀x)
- x − 1 ≥ I n x ( x > 0 ) x-1 \geq Inx\quad (x>0) x−1≥Inx(x>0)
- x > s i n x ( x > 0 ) x> sinx\quad (x>0) x>sinx(x>0)
- 1 1 + x < I n ( 1 + 1 x ) < 1 x \frac{1}{1+x}<In(1+\frac{1}{x})<\frac{1}{x} 1+x1<In(1+x1)<x1
- x 1 + x < I n ( 1 + x ) < x \frac{x}{1+x}<In(1+x)<x 1+xx<In(1+x)<x
- a b ≤ a + b 2 ≤ a 2 + b 2 2 ( a , b > 0 ) \sqrt{ab}\leq \frac{a+b}{2}\leq \sqrt{\frac{a^2+b^2}{2}}\quad (a,b>0) ab≤2a+b≤2a2+b2(a,b>0)
- a b c 3 ≤ a + b + c 3 ( a , b , c > 0 ) \sqrt[3]{abc}\leq \frac{a+b+c}{3}\quad (a,b,c>0) 3abc≤3a+b+c(a,b,c>0)
- ∣ a ± b ∣ ≤ ∣ a ∣ + ∣ b ∣ \mid a\pm b\mid \leq \mid a\mid + \mid b\mid ∣a±b∣≤∣a∣+∣b∣
- ∣ ∣ a ∣ − ∣ b ∣ ∣ ≤ ∣ a − b ∣ \mid \mid a\mid - \mid b\mid \mid \leq \mid a-b\mid ∣∣a∣−∣b∣∣≤∣a−b∣
- ∣ ∫ a b f ( x ) d x ∣ ≤ ∫ a b ∣ f ( x ) ∣ d x \mid \int_a^bf(x)dx\mid \leq \int_a^b\mid f(x)\mid dx ∣∫abf(x)dx∣≤∫ab∣f(x)∣dx
5 三角变换
- 诱导公式法则:奇变偶不变,符号看象限!
- s i n 2 x = 2 s i n x c o s x sin2x = 2sinxcosx sin2x=2sinxcosx
- c o s 2 x = c o s 2 x − s i n 2 x = 1 − 2 s i n 2 x = 2 c o s 2 − 1 cos2x = cos^2x - sin^2x = 1-2sin^2x = 2cos^2-1 cos2x=cos2x−sin2x=1−2sin2x=2cos2−1
- s i n 3 x = − 4 s i n 3 x + 3 s i n x sin3x = -4sin^3x + 3sinx sin3x=−4sin3x+3sinx
- c o s 3 x = 4 c o s 2 x − 3 c o s x cos3x = 4cos^2x - 3cosx cos3x=4cos2x−3cosx
- s i n x ⋅ c o s y = 1 2 [ s i n ( x + y ) + s i n ( x − y ) ] sinx\cdot cosy = \frac{1}{2}[sin(x+y)+sin(x-y)] sinx⋅cosy=21[sin(x+y)+sin(x−y)]
- s i n 2 x 2 = 1 2 ( 1 − c o s x ) sin^2\frac{x}{2} = \frac{1}{2}(1-cosx) sin22x=21(1−cosx)
- c o s 2 x 2 = 1 2 ( 1 + c o s x ) cos^2\frac{x}{2} = \frac{1}{2}(1+cosx) cos22x=21(1+cosx)
- t a n 2 x 2 = 1 − c o s x s i n x = s i n x 1 + c o s x tan^2\frac{x}{2} = \frac{1-cosx}{sinx} = \frac{sinx}{1+cosx} tan22x=sinx1−cosx=1+cosxsinx
- s i n x = 2 t a n x 2 1 + t a n 2 x 2 sinx = \frac{2tan\frac{x}{2}}{1+tan^2\frac{x}{2}} sinx=1+tan22x2tan2x
- c o s x = 1 − t a n 2 x 2 1 + t a n 2 x 2 cosx = \frac{1-tan^2\frac{x}{2}}{1+tan^2\frac{x}{2}} cosx=1+tan22x1−tan22x
- t a n 2 x = 2 t a n x 1 − t a n 2 x tan2x = \frac{2tanx}{1-tan^2x} tan2x=1−tan2x2tanx
- c o t 2 x = c o t 2 x − 1 2 c o t x cot2x = \frac{cot^2x - 1}{2cotx} cot2x=2cotxcot2x−1
- 1 + t a n 2 x = s e c 2 x 1+tan^2x = sec^2x 1+tan2x=sec2x
- 1 + c o t 2 x = c s c 2 x 1+cot^2x = csc^2x 1+cot2x=csc2x
6 * \bigstar *微分 * \bigstar *
6.1 定义式
- f ′ ( x 0 ) = lim Δ x → 0 f ( x 0 + Δ x ) − f ( x 0 ) Δ x = lim x → x 0 f ( x ) − f ( x 0 ) x − x 0 f'(x_0) = \lim\limits_{\Delta x\to{0}}\frac{f(x_0 + \Delta x) - f(x_0)}{\Delta x} = \lim\limits_{x\to{x_0}}\frac{f(x) - f(x_0)}{x-x_0} f′(x0)=Δx→0limΔxf(x0+Δx)−f(x0)=x→x0limx−x0f(x)−f(x0)
- f ( n ) ( x 0 ) = lim x → x 0 f ( n − 1 ) ( x ) − f ( n − 1 ) ( x 0 ) x − x 0 f^{(n)}(x_0) = \lim\limits_{x\to{x_0}} \frac{f^{(n-1)}(x) - f^{(n-1)}(x_0)}{x-x_0} f(n)(x0)=x→x0limx−x0f(n−1)(x)−f(n−1)(x0)
- 连续 ⇏ \nRightarrow ⇏ 可导,可导 ⇒ \Rightarrow ⇒ 连续,可导 ⇔ \Leftrightarrow ⇔ 可微
6.2 常用难记微分公式
- ( t a n x ) ′ = s e c 2 x (tanx)' = sec^2x (tanx)′=sec2x
- ( c o t x ) ′ = − c s c 2 x (cotx)' = -csc^2x (cotx)′=−csc2x
- ( s e c x ) ′ = s e c x t a n x , ( c s c x ) ′ = − c s c x c o t x (secx)' = secxtanx, (cscx)' = -cscxcotx (secx)′=secxtanx,(cscx)′=−cscxcotx
- ( a r c s i n x ) ′ = 1 1 − x 2 , ( a r c c o s x ) ′ = − 1 1 − x 2 (arcsinx)' = \frac{1}{\sqrt{1-x^2}},\quad (arccosx)' = -\frac{1}{\sqrt{1-x^2}} (arcsinx)′=1−x21,(arccosx)′=−1−x21
- ( a r c t a n x ) ′ = 1 1 + x 2 , ( a r c c o t x ) ′ = − 1 1 + x 2 (arctanx)' = \frac{1}{1+x^2},\quad (arccotx)' = -\frac{1}{1+x^2} (arctanx)′=1+x21,(arccotx)′=−1+x21
- ( I n ∣ c o s x ∣ ) ′ = − t a n x (In\mid cosx\mid)' = -tanx (In∣cosx∣)′=−tanx
- ( I n ∣ s i n x ∣ ) ′ = c o t x (In\mid sinx\mid)' = cotx (In∣sinx∣)′=cotx
- ( I n ∣ s e c x + t a n x ∣ ) ′ = s e c x (In\mid secx + tanx\mid)' = secx (In∣secx+tanx∣)′=secx
- ( I n ∣ c s c x − c o t x ∣ ) ′ = c s c x (In\mid cscx - cotx\mid)' = cscx (In∣cscx−cotx∣)′=cscx
- [ I n ( x + x 2 ± a 2 ) ] ′ = 1 x 2 ± a 2 [In(x+\sqrt{x^2\pm a^2})]' = \frac{1}{\sqrt{x^2\pm a^2}} [In(x+x2±a2)]′=x2±a21
- d x 2 = ( d x ) 2 dx^2 = (dx)^2 dx2=(dx)2
- d ( x 2 ) = 2 x d x d(x^2) = 2xdx d(x2)=2xdx
- ( u v w ) ′ = u ′ v w + u v ′ w + u v w ′ (uvw)' = u'vw+uv'w+uvw' (uvw)′=u′vw+uv′w+uvw′
- ( u v ) ( n ) = ∑ k = 0 n C n k u ( n − k ) v ( k ) (uv)^{(n)} = \sum\limits_{k=0}^{n}C_n^ku^{(n-k)}v^{(k)} (uv)(n)=k=0∑nCnku(n−k)v(k)
6.3 分析函数关注点
定义域、奇偶性、对称性、图形变换、单调性、极值、最值、凹凸性、拐点、三种渐近线(铅垂、水平、斜)
7 * \bigstar *积分 * \bigstar *
7.1 定积分定义
- ∫ a b f ( x ) d x = lim n → ∞ ∑ i = 1 ∞ f ( a + b − a n i ) b − a n \int_a^bf(x)dx =\lim\limits_{n\to{\infty}} \sum\limits_{i=1}^{\infty} f(a+\frac{b-a}{n}i)\frac{b-a}{n} ∫abf(x)dx=n→∞limi=1∑∞f(a+nb−ai)nb−a
- ∫ 0 1 f ( x ) d x = lim n → ∞ ∑ i = 1 ∞ f ( i n ) 1 n \int_0^1f(x)dx =\lim\limits_{n\to{\infty}} \sum\limits_{i=1}^{\infty} f(\frac{i}{n})\frac{1}{n} ∫01f(x)dx=n→∞limi=1∑∞f(ni)n1
- ∫ 0 x f ( x ) d x = lim n → ∞ ∑ i = 1 ∞ f ( x n i ) x n \int_0^xf(x)dx =\lim\limits_{n\to{\infty}} \sum\limits_{i=1}^{\infty} f(\frac{x}{n}i)\frac{x}{n} ∫0xf(x)dx=n→∞limi=1∑∞f(nxi)nx
7.2 基本积分表
- ∫ x k d x = 1 k + 1 x k + 1 + C \int x^k dx = \frac{1}{k+1}x^{k+1} + C ∫xkdx=k+11xk+1+C
- ∫ a x d x = a x I n a + C \int a^x dx = \frac{a^x}{Ina} +C ∫axdx=Inaax+C
- ∫ s i n x d x = − c o s + C \int sinx dx = -cos +C ∫sinxdx=−cos+C
- ∫ c o s d x = s i n x + C \int cos dx = sinx +C ∫cosdx=sinx+C
- ∫ t a n x d x = − I n ∣ c o s x ∣ + C \int tanx dx = -In\mid cosx\mid +C ∫tanxdx=−In∣cosx∣+C
- ∫ c o t x d x = I n ∣ s i n x ∣ + C \int cotx dx = In\mid sinx\mid +C ∫cotxdx=In∣sinx∣+C
- ∫ s e c x d x = I n ∣ s e c x + t a n x ∣ + C \int secx dx = In\mid secx + tanx\mid +C ∫secxdx=In∣secx+tanx∣+C
- ∫ c s c x d x = I n ∣ c s c x − c o t x ∣ + C \int cscx dx = In\mid cscx - cotx\mid +C ∫cscxdx=In∣cscx−cotx∣+C
- ∫ s e c 2 x d x = t a n x + C \int sec^2x dx = tanx +C ∫sec2xdx=tanx+C
- ∫ c s c 2 x d x = − c o t x + C \int csc^2x dx = -cotx +C ∫csc2xdx=−cotx+C
- ∫ s e c x t a n x d x = s e c x + C \int secxtanx dx = secx +C ∫secxtanxdx=secx+C
- ∫ c s c x c o t x d x = − c s c x + C \int cscxcotx dx = -cscx +C ∫cscxcotxdx=−cscx+C
- ∫ 1 1 − x 2 d x = a r c s i n x + C \int \frac{1}{\sqrt{1-x^2}} dx = arcsinx +C ∫1−x21dx=arcsinx+C
- ∫ 1 a 2 − x 2 d x = a r c s i n x a + C \int \frac{1}{\sqrt{a^2-x^2}} dx = arcsin\frac{x}{a} +C ∫a2−x21dx=arcsinax+C
- ∫ 1 1 + x 2 d x = a r c t a n x + C \int \frac{1}{1+x^2} dx = arctanx +C ∫1+x21dx=arctanx+C
- ∫ 1 a 2 + x 2 d x = 1 a a r c t a n x a + C ( a > 0 ) \int \frac{1}{a^2+x^2} dx = \frac{1}{a}arctan\frac{x}{a} +C\quad (a>0) ∫a2+x21dx=a1arctanax+C(a>0)
- ∫ 1 x 2 + a 2 d x = I n ( x + x 2 + a 2 ) + C \int \frac{1}{\sqrt{x^2+a^2}} dx = In(x+\sqrt{x^2+a^2}) +C ∫x2+a21dx=In(x+x2+a2)+C
- ∫ 1 x 2 − a 2 d x = I n ( x + x 2 − a 2 ) + C ( ∣ x ∣ > ∣ a ∣ ) \int \frac{1}{\sqrt{x^2-a^2}} dx = In(x+\sqrt{x^2-a^2}) +C\quad (\mid x\mid>\mid a\mid) ∫x2−a21dx=In(x+x2−a2)+C(∣x∣>∣a∣)
- ∫ 1 x 2 − a 2 d x = 1 2 a I n ∣ x − a x + a ∣ + C \int \frac{1}{x^2-a^2} dx = \frac{1}{2a}In\mid \frac{x-a}{x+a}\mid +C ∫x2−a21dx=2a1In∣x+ax−a∣+C
- ∫ 1 a 2 − x 2 d x = 1 2 a I n ∣ x + a x − a ∣ + C \int \frac{1}{a^2-x^2} dx = \frac{1}{2a}In\mid \frac{x+a}{x-a}\mid +C ∫a2−x21dx=2a1In∣x−ax+a∣+C
- ∫ a 2 − x 2 d x = a 2 2 a r c s i n x a + x 2 a 2 − x 2 + C ( ∣ x ∣ < a ) \int \sqrt{a^2-x^2} dx = \frac{a^2}{2}arcsin\frac{x}{a} + \frac{x}{2}\sqrt{a^2-x^2} +C\quad (\mid x\mid<a) ∫a2−x2dx=2a2arcsinax+2xa2−x2+C(∣x∣<a)
- ∫ s i n 2 x d x = x 2 − s i n 2 x 4 + C \int sin^2x dx = \frac{x}{2} -\frac{sin2x}{4} +C ∫sin2xdx=2x−4sin2x+C
- ∫ c o s 2 x d x = x 2 + s i n 2 x 4 + C \int cos^2x dx = \frac{x}{2} +\frac{sin2x}{4} +C ∫cos2xdx=2x+4sin2x+C
7.3 常用积分公式
- ∫ a b f ( x ) d x = ∫ a b f ( a + b − x ) d x \int_a^b f(x) dx = \int_a^b f(a+b-x) dx ∫abf(x)dx=∫abf(a+b−x)dx
- ∫ a b f ( x ) d x = 1 2 ∫ a b [ f ( x ) + f ( a + b − x ) ] d x \int_a^b f(x) dx = \frac{1}{2} \int_a^b [f(x)+f(a+b-x)] dx ∫abf(x)dx=21∫ab[f(x)+f(a+b−x)]dx
- ∫ a b f ( x ) d x = ∫ a a + b 2 [ f ( x ) + f ( a + b − x ) ] d x \int_a^b f(x) dx = \int_a^{\frac{a+b}{2}} [f(x)+f(a+b-x)] dx ∫abf(x)dx=∫a2a+b[f(x)+f(a+b−x)]dx
- 点火公式: ∫ 0 π 2 s i n n x d x = ∫ 0 π 2 c o s n x d x = n − 1 n n − 3 n − 2 ⋯ \int_0^\frac{\pi}{2}sin^nxdx = \int_0^\frac{\pi}{2}cos^nxdx = \frac{n-1}{n} \frac{n-3}{n-2} \cdots ∫02πsinnxdx=∫02πcosnxdx=nn−1n−2n−3⋯
- ∫ 0 π x f ( s i n x ) d x = π 2 ∫ 0 π f ( s i n x ) d x = π ∫ 0 π 2 f ( s i n x ) \int_0^{\pi} xf(sinx) dx = \frac{\pi}{2}\int_0^{\pi} f(sinx) dx =\pi \int_0^{\frac{\pi}{2}} f(sinx) ∫0πxf(sinx)dx=2π∫0πf(sinx)dx=π∫02πf(sinx)
- ∫ 0 π 2 f ( s i n x ) d x = ∫ 0 π 2 f ( c o s x ) d x \int_0^{\frac{\pi}{2}} f(sinx) dx = \int_0^{\frac{\pi}{2}} f(cosx) dx ∫02πf(sinx)dx=∫02πf(cosx)dx
- ∫ 0 π 2 f ( s i n x , c o s x ) d x = ∫ 0 π 2 f ( c o s x , s i n x ) d x \int_0^{\frac{\pi}{2}} f(sinx, cosx) dx = \int_0^{\frac{\pi}{2}} f(cosx,sinx) dx ∫02πf(sinx,cosx)dx=∫02πf(cosx,sinx)dx
- ∫ a b f ( x ) d x = ∫ − π 2 π 2 f ( a + b 2 + b − a 2 s i n t ) ⋅ b − a 2 c o s t d t , ( x − a + b 2 = b − a 2 s i n t ) \int_a^b f(x) dx = \int_{-\frac{\pi}{2}}^{\frac{\pi}{2}} f(\frac{a+b}{2} + \frac{b-a}{2} sint)\cdot \frac{b-a}{2}cost dt, \quad (x-\frac{a+b}{2} = \frac{b-a}{2}sint) ∫abf(x)dx=∫−2π2πf(2a+b+2b−asint)⋅2b−acostdt,(x−2a+b=2b−asint)
- ∫ a b f ( x ) d x = ∫ 0 1 ( b − a ) f [ a + ( b − a ) t ] d t , ( x − a = ( b − a ) t ) \int_a^b f(x) dx = \int_{0}^{1} (b-a) f[a+(b-a)t] dt, \quad (x-a = (b-a)t) ∫abf(x)dx=∫01(b−a)f[a+(b−a)t]dt,(x−a=(b−a)t)
- ∫ − a a f ( x ) d x = ∫ 0 a [ f ( x ) + f ( − x ) ] d x \int_{-a}^a f(x) dx = \int_{0}^{a} [f(x) + f(-x)] dx ∫−aaf(x)dx=∫0a[f(x)+f(−x)]dx
- ∫ 0 n π x ∣ s i n x ∣ d x = n 2 π \int_0^{n\pi} x\mid sinx\mid dx = n^2\pi ∫0nπx∣sinx∣dx=n2π
7.4 积分常用方法
凑微分、换元、分部积分、通分
全部手打,如果觉得有帮助帮忙点个赞啦蟹蟹!之后会继续补全高数下的公式,可以先收藏哦。
边栏推荐
- acwing 843. n-皇后问题
- 【数模】Matlab allcycles()函数的源代码(2021a之前版本没有)
- National meteorological data / rainfall distribution data / solar radiation data /npp net primary productivity data / vegetation coverage data
- STM32F103实现IAP在线升级应用程序
- STM32 encapsulates the one key configuration function of esp8266: realize the switching between AP mode and sta mode, and the creation of server and client
- 【愚公系列】2022年7月 Go教学课程 005-变量
- 【736. Lisp 语法解析】
- JS variable plus
- DFS and BFS concepts and practices +acwing 842 arranged numbers (DFS) +acwing 844 Maze walking (BFS)
- Introduction to the PureMVC series
猜你喜欢
随机推荐
Appium practice | make the test faster, more stable and more reliable (I): slice test
当 Knative 遇见 WebAssembly
Vscode 如何使用内置浏览器?
Monitoring cannot be started after Oracle modifies the computer name
A detailed explanation of head pose estimation [collect good articles]
Vscode automatically adds a semicolon and jumps to the next line
When knative meets webassembly
ServiceMesh主要解决的三大痛点
Using thread class and runnable interface to realize the difference between multithreading
Introduction to namespace Basics
Oracle - views and sequences
Camera calibration (I): robot hand eye calibration
A picture to understand! Why did the school teach you coding but still not
STM32F103 realize IAP online upgrade application
指针与数组在函数中输入实现逆序输出
Meow, come, come: do you really know if, if else
Organize five stages of actual attack and defense drill
STM32F103ZE+SHT30检测环境温度与湿度(IIC模拟时序)
Wechat can play the trumpet. Pinduoduo was found guilty of infringement. The shipment of byte VR equipment ranks second in the world. Today, more big news is here
The most complete learning rate adjustment strategy in history LR_ scheduler